Black Holes: A Very Short Introduction - Blundell, Katherine M (New York Oxford University Press, 2015)
Black holes are a constant source of fascination to many due to their mysterious nature. In this Very Short Introduction, Katherine Blundell addresses a variety of questions, including what a black hole actually is, how they are characterized and discovered, and what would happen if you came too close to one. She explains how black holes form and grow - by stealing material that belongs to stars, as well as how many there may be in the Universe. She also explores the large black holes found in the centres of galaxies, and how black holes give rise to quasars and other spectacular phenomena in the cosmos.
Includes Index and Illustrations.
Keywords: Black holes (Astronomy)